Opportunities in accounting - Lodge, Arthur (Ky: Vocational Guidance Manuals : Louisville, 1977)
Surveys the scope and history of accounting and discusses the education and training necessary to enter the field, types of jobs, and professional organizations.
Includes index.
Bibliography: p. 119
Keywords: Accounting -- Vocational guidance -- Juvenile literature